Competitive sports and the heart: benefit or risk? - Scharhag, Jürgen; Löllgen, Herbert; Kindermann, Wilfried (Deutsches Ärzteblatt, 2013)
Physicians of the ancient and early modern world often recommended physical exercise as a means of staying healthy. Today, various medical specialty societies recommend exercise and athletic activity to maintain and preserve health, on the basis of...